Phytochemical analysis and nephroprotective potential of Ajwa date in doxorubicin‐induced nephrotoxicity rats: Biochemical and molecular docking approaches. Issue 3 (27th January 2023) - Baothman, Othman A. S.; Altayb, Hisham N.; Zeyadi, Mustafa A.; Hosawi, Salman B.; Abo‐Golayel, Mohamed Kamel
Abstract: The purpose of this study is to evaluate the likely defensive impact of Ajwa date aqueous extract (AJDAE) in alleviating the nephrotoxicity generated by doxorubicin (DOX) injection in rats. Sixty male Wister albino rats were randomly and equally separated into six groups ( n = 10), and they were treated as follows: untreated control group, extract groups administered with 0.75 and 1.5 mg kg bw of AJDAE, toxicant control group administered with DOX, and prophylactic groups were treated with 0.75 and 1.5 mg/kg of AJDAE and 15 mg/kg DOX. Biochemical parameters, antioxidant enzymes, renal functions, DNA integrity, and histopathology were studied to evaluate the nephroprotective activity of AJDAE. Furthermore, bioactive compounds were utilized for in silico molecular docking. AJDAE treatment resulted in significant improvements in the amended renal biomarkers (urea, creatinine, calcium, phosphorous, and uric acid), antioxidative markers, and MDA. Noticeable histopathological improvements supported this result. Results of in silico studies revealed that d ‐Mannitol, 6TMS derivative, palmitic acid, and TMS derivative had a higher docking score with human soluble epoxide hydrolase (−10.9 kcal/mol) and NF‐κB‐DNA (−7 kcal/mol). The present findings indicated that AJDAE could decrease ROS generation and lipid peroxidation (LPO) and repair the DOX injection‐related DNA damage. Abstract : The nephroprotective effect of the Ajwa date extract could be attributed to its potential antioxidant effect that contains phytochemicals with potential therapeutic value for the nephrotoxicity.